Mosquitoes (Diptera: Culicidae) originally described from French Guiana - Talaga, Stanislas; Gantier, Jean-Charles; Girod, Romain (Zootaxa, 2020)
Examination of type specimens and topotypic material is often a necessary step to ascertain the validity of a species. Consequently, solid knowledge about type series, type locality and type depository is critical. In this paper, we provide a thorough review of the mosquito species originally described from specimens collected in French Guiana, with specific emphasis on the location of the current depositories of type material, the composition of type series and the delimitation of type localities. Information already published about the mosquito type material from French Guiana was gathered and efforts were made to ascertain the current location of their depositories. This investigation made it possible to locate a large part of the existing type material and to provide corrected information on type series and type localities, therefore providing a strong basis for future taxonomic research on mosquitoes. The type locality of Culex (Culex) pseudojanthinosoma Senevet & Abonnenc is corrected from French Guiana to Africa, and this species is synonymized with Culex (Culex) duttoni Theobald.